Multi-scale, social-ecological influences on private land conservation in South Africa - Clements, Hayley S (Percy FitzPatrick Institute of African Ornithology, 2017)
In understanding the behaviour of social-ecological systems, much focus has been placed on the role of institutions that govern how natural resources should be managed, and the biophysical processes affected by this management. Somewhat less attention has been given to the role played by the natural resource managers themselves. Novel insight into social-ecological systems can be gained from understanding why managers act as they do and how management actions become reinforced into (un)sustainable management regimes. In this thesis I applied a social-ecological systems perspective to the phenomenon of private land conservation. With increasing interest in the role that the private sector can play in global conservation efforts, a pertinent but largely unexplored question is whether private land conservation areas (PLCAs) can conserve biodiversity over sufficiently long time scales. This thesis contributes to social-ecological systems theory through an in-depth analysis of the multi-scale interactions among natural resources, managers and socioeconomic processes, which affect PLCA management practices and their sustainability. The potential ability for commercially operated PLCAs to generate the funds necessary for their maintenance makes them an attractive conservation strategy in an economically-orientated world. There are concerns, however, that (a) their long-term sustainability may be dependent on their ability to become and remain financially viable; and (b) they may be tempted to prioritize profit over biodiversity protection in their management practices, thereby jeopardizing their ecological sustainability. The objectives of this thesis were to investigate if, how and why commercial PLCA managers (a) meet their financial objectives and (b) adopt unsustainable ecological management practices. During 2014 and 2015 I interviewed the managers of 72 commercial PLCAs in the Western and Eastern Cape Provinces of South Africa, a region that supports a rapidly growing yet poorly understood PLCA industry. I applied theories from organizational ecology to understand patterns in the income-generating strategies adopted by PLCA managers. Distinct business models were evident, differentiated by incompatibilities in the biophysical (size, fauna) and socioeconomic (activities, affordability) characteristics of these conservation areas. PLCAs characterized by financial objectives but unprofitable business models suggest that these incompatibilities constrain the ability of managers to effectively adapt to their economic environment, a concept known as "structural inertia" in organizational ecology. Profitability was highest on PLCAs that supported megaherbivores and large predators, reflecting international tourist preferences for charismatic game. Managers' financial objectives influenced the strategies that they employed to manage these mammals. When managers used revenue-generation to inform their management decisions, they undertook management actions that enabled them to maximize and stabilize game populations. While this intensive management resulted in higher revenues, it corresponded in many cases with a lack of ecological monitoring and an increased risk of overstocking game. Regional policy guidelines for large predator management both mitigated and exacerbated the mismatch between financially-desirable and ecologically-sustainable management, depending on whether species-specific guidelines were ecologically appropriate or not. Simulations of a mechanistic PLCA model were used to test whether adopted management strategies influenced the observed constraints on business model adaptation. If the income-generating potential of an adopted business model was low, managers were unable to accumulate the capital necessary to overcome the biophysical and socioeconomic incompatibilities that separated business models, constraining their adaptive capacity. Intensively managed PLCAs were able to generate a more stable annual income, accumulate more capital and overcome constraints on adaptation faster than PLCAs managed according to ecological monitoring. This unique, large-sample assessment of the social-ecological mechanisms underlying PLCA sustainability emphasizes the significant role that managers can play in promoting resilient social-ecological systems. When financial viability is an important consideration, broad-scale socioeconomic factors can influence fine-scale management decisions. Through constraints on adaptation, and the presence or absence of corrective feedbacks between management actions and ecological monitoring, these management decisions can become reinforced into management regimes on a trajectory towards, or away from, sustainability. This study therefore provides a novel contribution to our understanding of how the interactions between managers and ecosystems influence the behaviour of social-ecological systems.